Family Adjustment in Relation to the Academic Engagement of Pupils at Primary Level - Abdullah, Tauqeer (Revija za elementarno izobraževanje, 2024)
Family adjustment is crucial for the child’s school obligations. This quantitative study was conducted to determine the significant relationship between the family adjustment of primary school pupils and their academic engagement. The pupils’ level of family adjustment was found to be positively and significantly related to their academic engagement (r = 619, p
Keywords: family adjustment, academic engagement, primary education, teacher, pupil.